Modelo de priorização da manutenção corretiva em ambientes hospitalares - Pazeto, Ana Caroline (2016)
This work presents a prioritization model of corrective maintenance in Health Care Facilities (HCR) with the aim of improving the service provide by the Clinical Engineering setor and increasing the availability of medical equipment (ME). The study was conducted in the Hospital of the Federal University of Uberlandia (HCUUFU) and in a Unit managed by Formedical. The methodology used was the creation of an equation to sort the EMAs and then an algorithm that relate the values of the equation and criteria specifics of each unit. The prioritization equation uses criteria like: ME Value, Financial resources, ME importance, programmed Services and a ANVISA's prioritization rule. The other criterions of the model was: critical Setor, ME Backup, Maximum time for the ME to stay in line, Unexpected events and Particularities. After creating the model, tests were performed on both units. For analysis of the results was made an comparison between the data collected from managements systems in the months of September, October and November of 2015 and the application of the model. This comparison generated an rate of agreement in the three months analyzed of 91,21% in HCU-UFU and 96,48% in Formedical. Thus, the results show that the proposed model is suitable for prioritization corrective maintenance in the analyzed HCRs.